Phlorofucofuroeckol-A: A Natural Compound with Potential to Attenuate Inflammatory Diseases Caused by Airborne Fine Dust - Eun-Gyeong Lee; Sung-Kun Yim; Sang-Min Kang; Byung Jae Ahn; Chang-Kwon Kim; Mina Lee; Dongseob Tark; Gun-Hee Lee (Medicina)
Background and Objectives: Persistent exposure to airborne fine dust (FD) particles contributing to air pollution has been linked to various human health issues, including respiratory inflammation, allergies, and skin diseases. We aimed to identify potential seaweed anti-inflammatory bioactive reagents and determine their effects on systemic inflammatory responses induced by FD particles. Materials and Methods: While exploring anti-inflammatory bioactive reagents, we purified compounds with potential anti-inflammatory effects from the seaweed extracts of Ecklonia cava, Ecklonia stolonifera, and Codium fragile. Structural analyses of the purified compounds siphonaxanthin (Sx), fucoxanthin (Fx), dieckol (Dk), and phlorofucofuroeckol-A (PFF-A) were performed using NMR and LC-MS/MS. Results: Notably, these compounds, especially PFF-A, showed significant protective effects against FD-induced inflammatory responses in RAW 264.7 cells without cytotoxicity. Further investigation of inflammatory-associated signaling demonstrated that PFF-A inhibited IL-1β expression by modulating the NF-κB/MAPK signal pathway in FD-induced RAW 264.7 cells. Additionally, gene profiling revealed the early activation of various signature genes involved in the production of inflammatory cytokines and chemokines using gene profiling. Treatment with PFF-A markedly reduced the expression levels of pro-inflammatory and apoptosis-related genes and even elevated the Bmp gene families. Conclusions: These results suggested that PFF-A is a potential natural therapeutic candidate for managing FD-induced inflammatory response.